PENGARUH KECERDASAN INTELEKTUAL TERHADAP KINERJA AKUNTAN PENDIDIK PADA JURUSAN AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS HALU OLEO - Mulyati Akib; Nur Asni (EKONOMI & SOSIAL, 2016)
This research aimed of presented to examine the effect of intellectual intellegence on the performance of educator accountant. Primary data in this research were obtained from the perseption off all lecturers and 76 generation students majoring 2013/2014 in Departement of Accountancy Economy faculty and Business Halu Oleo University. Preceptions in measured by responses to ques tionnaires that uses ordinal measurement with a 5 point Likert scale. The analytical tool used to test the hypotesis is simple linear regression analysis with the help software IBM Statistical Package for Social Sciencess (SPSS) Statistics Versi 22, with comparing the answers of respondents are students and lecturers.The results of this research indicate that intellectual intellegence significantly effect on the performance of educator accountant. The results of the coefficient of determination for intellectual intellegence in R2 = 0,664 dan 0,748. This number can be used to see the contribution of intellectual intellegence on the performance of educator accountant is 66,4% and 74,8%, while the remaining 33,6% and 25,2% was obtained from the contribution of other factors.